Should whole body cryotherapy sessions be differentiated between women and men? A preliminary study on the role of the body thermal resistance. (November 2018) - Polidori, G.; Cuttell, S.; Hammond, L.; Langdon, D.; Legrand, F.; Taiar, R.; Boyer, F.C.; Costello, J.T.
Abstract: The aim of this study was to investigate how body thermal resistance between sexes evolves over time in the recovery period after a WBC session and to show how this parameter should be considered as a key parameter in WBC protocols. Eighteen healthy participants volunteered for the study (10 males and 8 females). Temperature (core and skin) were recorded pre- and post (immediately and every 5 min until 35 min post) exposure to a single bout of WBC (30 s at −60 °C, 150 s at −110 °C). From both core and skin temperatures a bio-heat transfer model was applied which led to the analytical formulation of the body thermal resistance. An unsteady behavior presenting a similar time-evolution trend in the body insulative response is shown for both females and males, possibly due to the vasodilatation process following an intense peripheral vasoconstriction during the extreme cold. Females present a 37% higher inner thermal resistance than males when reaching an asymptotical thermal state at rest due to a higher concentration of body fat percentage. Adiposity of tissues inherent in fat mass percentage appears to be a key parameter in the body thermal resistance to be taken into account in the definition of appropriate protocols for males and females. The conclusions of this preliminary study suggest that in order to achieve the same skin effects on temperature and consequently to cool efficiency tissues in the same way, the duration of cryotherapy protocols should be shorter when considering female compared to male.